The ImageStream System: a key step to a new era in imaging. - James W Lillard; Ahmed Abdel-Latif; Magdalena Kucia; Ewa K Zuba-Surma; Mariusz Z Ratajczak (Folia Histochemica et Cytobiologica, 2008)
The aim of this article is to provide a brief review about the ImageStream system a novel tool for multiparameter cell analysis in flow. The instrument integrates the features of flow cytometry and fluorescence microscopy combined with a modern methodology for image analysis. Similar to flow cytometry, ImageStream allows analysis of a large number of cells based on their fluorescence features and provides statistical analysis of these features. Additionally, ImageStream allows detailed morphometric cellular analysis based on acquired cellular images integrating various morphometric and photometric features of the examined cells. Simply stated, ImageStream system is an advanced flow cytometer acquiring both integrated fluorescence signals as well as high quality fluorescence images and allowing muliparameter analysis. The innovative features of the instrument offer new analytical capabilities and allow for a multitude of possible applications beyond the current means of flow cytometry. While this article summarizes basic information about the features of ImageStream and its applications based on the available literature and it also describes our own experience.